The sultan's entrepreneurs, the entrepreneurs’ sultan: Beratlı Avrupa Tüccarı and institutional change in the nineteenth century Ottoman Empire (1835-1868) - Kaymakcı, Said Salih. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
This thesis examines the Beratlı Avrupa Tüccarı, non-Muslim Ottoman merchants who engaged in trade with the special licenses issued in the name of the sultan in the nineteenth century. The research was primarily based on documents from the Prime Minister’s Office of the Ottoman Archives. The conclusions reached were when the state identified the prosperity of the country with the increase in trade and attributed itself the regulatory role for this and the merchants demanded the backing of the state in their trade and the necessary changes in the system, the institutional transformation of the Ottoman Empire was inevitable. This interaction was accompanied by the already increasing economic activity, which gave momentum to the merchant’s demands and the state’s willingness to change. Hence, the nineteenth century reforms in the commercial and legal fields had the imprint of the merchant practices, the state’s active policy-making and the environment of growing trade and economic growth.
Keywords: Minorities Turkey Economic conditions.; Turkey Commerce History.; Turkey History 1683-1829.